(untitled) (Journal of Asian Development Studies, 2025)
This thesis examines the impact of excessive social media usage on interpersonal relationships between Millennials (born 1981–1996) and Gen Z (born 1997–2012). Sixteen individuals participated, comprising eight males and eight females from both generations, providing a balanced perspective. An interview was conducted with individuals from both generations, comprising a sample size of N = 16 (8 males and 8 females), to gauge a balanced approach between the two generations. Data was collected through semi-structured interviews using open-ended questions. Interviews were transcribed, and a thematic analysis was conducted to identify patterns across the dataset. As a result, six themes emerged: Educational Institutions Incorporate Moral Dimensions, Role of Social Media in Daily Life, Primary Reason for Using Social Media, Face-to-Face Interaction, Communication Gap, and Online and Offline Relationship. This study’s conclusion shows that excessive usage of social media has deepened generational divides, created tension and disconnected between Millennial and Gen Z. This study adds to the continuing conversations, particularly, communicative gaps, emotional depth, and bridging the gap requires conscious efforts to balance online and offline interactions, alongside incorporating moral dimensions in education to foster healthier relationships and digital habits.